Is it true that Flash Sale and Free Shipping Tagline Affect Impulsive Buying Behavior of Lazada E-Commerce Users Living in Semarang? (Study on Lazada Marketplace Users in Semarang City) - Salsabila Hasna Kamilah; Erfiyanti; Anita Nurmaida Putri; Khairani Zikrinawati; Zulfa Fahmy (Experimental Student Experiences, 2024)
This study aims to determine the effect of flash sales tagline “free shipping on the impulsive buying behavior of Lazada e-commerce users who live in Semarang. The subject of this research is the Lazada application users who live in Semarang who were taken by purposive sampling technique. The measuring instrument in this study was an impulsive buying scale and a questionnaire regarding flash sales and the tagline "free shipping" with two answer choices. Impulse buying scale based on aspects of Rook. The results of this study indicate that there is a significant effect if tested partially between flash sale and impulsive buying variables with p=0.001, but if the tagline variable "free shipping" and impulsive buying produces a significance value of p=0.764, which means there is no significant relationship. If flash sales and free shipping tagline are tested simultaneously on impulsive buying, it produces a significance of p=0.000, which means that there is an influence between two variables on impulsive buying. Based on r square, a value of 0.151 is obtained so that the effect of flash sale and free shipping tagline simultaneously on impulsive buying is 15.1%. The rest is influenced by other variables that are outside this study.